Dynamic capabilities as an intermediary mechanism between digital transformation and institutional sustainability: An applied study at Algeria Telecom - Adel, Gherbi; Tamma, Elhachemi; Fateh, Serdouk; Khalida, Abi; Bachir, Benamor Mohammed (Journal of Ecohumanism, 2025)
This study aimed at analyzing the impact of digital transformation on organizational sustainability, examining the mediating role of dynamic capabilities, within the context of Algeria Telecom. The study was based on the hypothesis that digital transformation only translates into effective organizational sustainability through dynamic organizational capabilities that enable the organization to sense, capitalize on, and repurpose resources. The study employed a descriptive-analytical approach and a quantitative methodology. Data were collected via a questionnaire distributed to a sample of 200 employees. Data were analyzed using PLS-SEM structural equation modeling via SmartPLS software, with model quality assessment conducted prior to hypothesis testing. The results showed the absence of multicollinearity, with VIF values ​​being low (1.87–2.36). The results also revealed a significant positive impact of digital transformation on organizational sustainability (β = 0.246, p < 0.05) with a relatively small effect size. The impact of digital transformation on dynamic capabilities was strong (β = 0.533, R² = 0.64), and the impact of dynamic capabilities on organizational sustainability was also strong (β = 0.517, R² = 0.71). The study demonstrated a partial mediation of dynamic capabilities between digital transformation and organizational sustainability through a significant indirect effect (β = 0.276, p < 0.05). The results confirm that building dynamic capabilities is a crucial prerequisite for maximizing the sustainable return on digital transformation in public institutions.